Whole exome sequencing: Applications in Prenatal Genetics - Jelin, Angie C. (Obstet Gynecol Clin North Am, 2018)
Prenatal whole exome sequencing (WES) has the potential to increase the ability to provide more diagnostic capabilities in fetuses with sonographic abnormalities which will then improve the ability to counsel families. It is also often the first step in improving the path towards informed diagnosis and treatment, which is especially important in the era of advancing in utero fetal therapy. In this review, we will discuss the current literature regarding prenatal WES, clinical indications for WES, challenges with interpretation/counseling (variants of unknown significance), research priorities, ethical issues, and potential future advances.